Using 6 questions cognitive method and polya’s model to helps students solve mathematical problem - Xinxin Li; Ying Zhou; Liwen Liang (Journal of Didactic Mathematics, 2021)
The ability to solve the mathematical equation problem is very important for the thinking development of middle school students.  “How to solve it” of George Polya is famous in the world. 6 questions cognitive model proposed by Professor Zhou are monitored through metacognition, and the 6 questions are coherent, complete and sequential. This paper found that the 6 questions cognitive model can help implement “How to solve it” of George Polya and reduce students' cognitive load. At the same time, this study found that 6 questions cognitive model can help students solve the mathematical equation problem better.